A Proposed Ethogram of Large-Carnivore Predatory Behavior, Exemplified by the Wolf - MacNulty, Daniel; Mech, L. David; Smith, Douglas (DigitalCommons@University of Nebraska - Lincoln, 2007)
Although predatory behavior is traditionally described by a basic ethogram composed of 3 phases (search, pursue, and capture), behavioral studies of large terrestrial carnivores generally use the concept of a ‘‘hunt’’ to classify and measure foraging. This approach is problematic because there is no consensus on what behaviors constitute a hunt. We therefore examined how the basic ethogram could be used as a common framework for classifying large carnivore behavior. We used >2,150 h of observed wolf (Canis lupus) behavior in Yellowstone National Park, including 517 and 134 encounters with elk (Cervus elaphus) and American bison (Bison bison), respectively, to demonstrate the functional importance of several frequently described, but rarely quantified, patterns of large carnivore behavior not explicitly described by the basic ethogram (approaching, watching, and attacking groups). To account for these additionally important behaviors we propose a modified form of the basic ethogram (search, approach, watch, attack-group, attack-individual, and capture). We tested the applicability of this ethogram by comparing it to 31 previous classifications and descriptions involving 7 other species and 5 other wolf populations. Close correspondence among studies suggests that this ethogram may provide a generally useful scheme for classifying large-carnivore predatory behavior that is behaviorally less ambiguous than the concept of a hunt.